Formação do Professor: vivencias e reflexões em Juruá-AM - Pinheiro, Jeová Gama (Brasil, 2024)
Based on studies, daily readings, bibliographical research and direct contact with the object of study through internships, this description aims to demonstrate in a descriptive way the course of supervised internships in the initial grades of Elementary Education, Early Childhood Education and Educational Management carried out in the public education network in the city of Juruá-Amazonas, covering two schools, and thus also had the description of the descriptive memorial that contributed to academic training and understanding of the teaching and learning process, educational challenges and pedagogical intervention. Bibliographical research was carried out, contact with the school environment, observation of its structure and organization, the reality in the classroom, led us to seek the development of proposed activities that encourage the student to participate, and the search for improving knowledge aimed at the education. With this, there was also the observation of pedagogical resources, the student evaluation process, the projects developed in the schools monitored through internships. The final result of the internships brought experience in this process. Early childhood education is the basis of education, while primary education pre-shapes the acquisition of reading and writing, just as educational management evaluates the development of teaching quality and seeks to improve education. The working methods in education are the most diverse in order to improve students' knowledge. This final course work brings with it the development of internships, contributing to educational training and scientific knowledge.